Bait preference by urban and suburban mammals in the port area Tanjung Priok, Jakarta, Indonesia - N. Sustriayu; B. L. Lim; A. Munif (Hemera Zoa, 1978)
Bait trials using burnt coconut, burnt saltfish and peanut butter for trapping urban rodent and insectivores were carried out at two residential areas and a rice field plot around Tanjung Priok, Jakarta from July to September 1977. Traps baited with cotton wool used as controls. Coconut was found to be a better bait than saltfish in residential areas, whilst both baits were observed to be equally as good in rice field. Peanut butter was least accepted in both habitats. Saltfish and coconut were found to be equally acceptable baits for R. r. diardii. Coconut was preferred to saltfish by R. r. norvegicus, and saltfish was preferred to coocnut by S. murinus, but R. argentiventer was shown to feed on coconut only. Baitpreference by individual species of rodents and insectivores in relation to their feeding behaviours was discussed. Overall results showed that coconut was the most effective bait followed by saltfish and least effective was peanut butter. Flavours of these baits as an additional attractant to house and field rats was also disecussed.